Bibliometric analysis of trends and development in religion and green tourism behavior - Precious Chikezie Ezeh; Kaitano Dube (Cogent Social Sciences)
Making use of Scopus indexed bibliometric data this study investigated the influence of religion on green tourism behaviour. Employing VOSviewer and Microsoft Excel as analytical tools, this study identified a gradual increase of publications in this area over the study period. This growth is believed to have been driven by environmental pressures such as pollution, climate change, adoption of SDGs and the outbreak of pandemics such as COVID-19. There seems to be an intense focus on studies that focus on understanding Islam and Christian religions’ influence in green purchasing behaviour, with evidence showing that these two religions play a central role in fostering a culture of environmental stewardship among followers. Religion significantly influences sustainability initiatives, promoting green purchasing intentions and ecological behaviors. The impact of other religions outside of main stream religions remains largely unknown. While study found a link between religion and purchasing behaviour It is unclear how tourism businesses utilize this information to attract religious-conscious tourists to their businesses. Despite the growing literature on religion and green tourism, there are substantial geographic and theoretical knowledge gaps regarding religion’s effect on green purchasing behavior, hindering effective marketing to this niche.